Successful treatment of trichomoniasis with tinidazole following desensitization in a patient allergic to metronidazole. (January 2021) - Biagi, Mark; Slipke, Wendy; Smalley, Alexa; Tsaras, Geoffrey
Metronidazole desensitization is recommended in patients with trichomoniasis and history of an allergic reaction to metronidazole due to presumed cross reactivity with tinidazole and lack of reliably safe and effective alternative therapies. We report our experiences in a patient with persistent trichomoniasis who failed to complete metronidazole desensitization due to a burning sensation over her whole body and pruritus but was later successfully desensitized to tinidazole without experiencing any adverse effects.